Enhancing ethical standards: a quantitative analysis of knowledge improvement a through structured good clinical practice workshop - Muthahanumaiah, Narasimha Murthy K.; Narasimahaiah, Manjunath G.; Mallikarjuna, Swamy R.; Reddy, Pesala Pavan Kumar (International Journal of Basic & Clinical Pharmacology, 2025)
Background: Good clinical practice (GCP) is an internationally recognized ethical and scientific quality standard for designing, conducting, recording, and reporting trials that involve the participation of human subjects. In India, postgraduate medical students are mandated to take part in research projects as part of their academic curriculum, but a lack of training leads to considerable disparity in their understanding of GCP principles. A structured educational intervention like the GCP workshop helps in filling these disparities and promotes the conduction of ethical research. Methods: An educational interventional study was conducted to assess the impact of a GCP workshop on knowledge among postgraduate medical students during a one-day GCP workshop at a tertiary care teaching hospital. A total of 163 students participated in the study. A self-developed, pre-validated questionnaire was used to assess the impact of knowledge before and after the workshop. Data was collected using Google forms and analysed by using Microsoft Excel and Jeffreys’s Amazing Statistics Program (JASP) software. Results: Out of 163 participants, 158 postgraduate students completed both pre- and post-tests. The mean pre-test score was 22.3±3.5, which increased to 24.5±0.9 in the post-test. To assess the normality of data distribution, the Shapiro-Wilk test was performed and resulted in p<0.001, indicating the use of a nonparametric test. Then the Wilcoxon signed-rank test was performed, and results indicated statistically significant improvement (Z=7.48, p<0.001). Question-wise analysis revealed an increase in accuracy from 87.06% to 98.36%, indicating improvement in knowledge across the questionnaires. Conclusions: The overall findings suggest that a structured good clinical practice (GCP) workshop plays a significant, important role in enhancing knowledge among postgraduate medical students.